The Pushcart prize XVI. - Henderson, Bill 1941-. ([Yonkers Pushcart Press.)
A yearly anthology of fiction, essays and poetry from the small presses chosen by writers. Included are Susan Onthank Mates' Theng, on refugees from Indochina, Joseph Novakovich's Honey in the Carcase, on the war in Yugoslavia, and Charles D'Ambrosio's Jacinta, on rural Oregon.
"Best of the small presses."
Editor: 1976/77- B. Henderson.
Title index, 1976/77-1980/81 in 1980/81; 1976/77-1986/87, in 1986/87.
Also available from Penguin in a paperback ed.
Keywords: American literature -- 20th century; Small presses -- United States